A STUDY OF SPEECH ACT BETWEEN SELLER AND BUYERS IN ‘SINAGA SHOP’ - Hilman Pardede; Herman (Universitas Wiralodra, 2020)
This research is aimed to investigate the speech act between seller and buyers in ‘Sinaga Shop’at Jalan Melanthon Siregar Pematangsiantar. Speech act is related to utterances. Communication can be said successful if the speech act between speaker and listener are good in daily life. The transaction in the market between seller and buyer is also inevitable. Therefore, the problem of this study is: “What kinds of speech act verbs do the sellers and buyers use in ‘SINAGA SHOP’ Jalan Melanthon Siregar Pematangsiantar in their daily conversational transaction? To answer the problem above, the researchers follow some theories that related with the problem, they are speech act theory by Austin (1962) and Searle (1985). Descriptive qualitative approach was conducted. Participants of this study are seller and buyers at “SINAGA SHOP”. They are female and male. Context of the study is the utterances of seller and buyers in “SINAGA SHOP”. After analyzing the data, the researchers found that there were some verbs that the seller and the buyer use in their daily transactional conversation, they are: Representative include suggest, report, state, inform, complain. Directive include ask, request, order. Expressive include apologize, thank, pardon. Commisive include offer and Declaratives include sentencing.illocutionary act, pragmatics, speech act, utterance